Simultaneous Occurring Heatwaves and Cyanobacteria Blooms Alter Polyunsaturated Fatty Acid Transfer in a Brackish Trophic Cascade - Alexander Wacker; Melanie E. Köhne; Laura M. Wienhausen; Ilka Carina Stephan (Journal of Marine Science and Engineering, 2026)
With climate change, marine heatwaves become more frequent and may favour the emergence of cyanobacterial blooms. Because cyanobacteria lack long-chain polyunsaturated fatty acids, they provide poor dietary quality for consumers, potentially altering the fatty acid composition of primary consumers and propagating nutritional stress through food webs. We examined how a simulated heatwave (12 °C to 18 °C) and an associated cyanobacterial bloom-like dominance may affect trophic transfer from phytoplankton to the herbivorous rotifer Brachionus plicatilis and further to its predator, the mysid Neomysis integer. Rotifers were fed either high-quality algae or a low-quality cyanobacteria-dominated diet mixture. Rotifers were then rinsed to remove external residual phytoplankton and subsequently offered as prey to mysids. We analyzed the fatty acid profiles of both rotifers and mysids and monitored mysid survival. High temperature and the presence of cyanobacteria at the base of the food web reduced mysid survival. Both factors also influenced the fatty acid composition of rotifers and mysids. For mysids at the third trophic level, warming modulated how strongly diet quality affected their fatty acid profile. These results suggest that concurrent heatwaves and cyanobacterial blooms may intensify cyanobacteria’s negative impacts on food webs by altering the transfer of key fatty acids across trophic levels.

Comparative risk factors among pancreatic adenocarcinoma patients vs. neuroendocrine and other pancreatic cancer patients - Daniel C. Beachler; Lauren E. Parlett; Jessica L. Petrick; Stephan Lanes; John Barron; David Debono; Michael J. Fisch (Cancer Causes & Control, 2026)

Mapping and quantifying nature’s contributions to people underpinning international food trade: the case of the Brazilian coffee and soy supply-chains - Gabriela Rabeschini; Antonio J. Castro; Abhishek Chaudhary; María R. Felipe-Lucia; Thomas Koellner; Kira Lancker; Alexandra Marques; Stephan Pfister; Catharina J. E. Schulp; Louise Willemen; Thomas Kastner (Sustainability Science, 2026)

Environmental uncertainty affects movement and space-use in sheep - Sarah T. Bartsch; William H. E. J. van Wettere; Simon C. Griffith; Stephan T. Leu (Behavioral Ecology and Sociobiology, 2026)
Animals regularly experience periods of food uncertainty due to seasonal changes and environmental variability. Further, the changing climate is leading to more variable weather patterns, which alter environmental conditions, and can result in resource distributions being less predictable in space and time. How animals respond to uncertain conditions, and in particular a changing distribution of food resources, remains largely unclear and is an important question in the field of movement and animal ecology. We used an experimental approach to study how Merino sheep ( Ovis aries ) respond to different levels of food location uncertainty in a drought-impacted region of the Australian arid zone. Sheep were unfamiliar with the experimental food locations at the start and progressively decreased their uncertainty (i.e., increased their environmental knowledge) when discovering an increasing number of foraging patches. We tracked 50 sheep with GPS collars (1 location every 15 s) and deduced their movement and space use behaviour. When food uncertainty decreased, individuals moved more directionally (greater step length, smaller turn angles) and moved greater distances per day. They also had larger daily ranges. Displacement (distance between first and last location of the day) increased once and otherwise remained similar across levels of uncertainty. Our study demonstrates how an arid zone ungulate, in a large 600 ha enclosed paddock, adjusted its movement and space use behaviour as it gained environmental information on food distribution. Our study provides important insights into how animals cope with variable environments in order to forage efficiently during periods of uncertainty. Significance statement Food distributions are often unpredictable over time, with climate change exacerbating variability. Understanding how animals respond to periods of environmental uncertainty is crucial to predict animal movement in space and time. We used an experimental approach and investigated how different levels of food location uncertainty affected the movement and space-use behaviour in sheep freely moving in a large 600 ha paddock. We used the number of discovered experimental food patches as a proxy for environmental knowledge (inverse of uncertainty). Movement was faster and more directional, and daily range size increased as food uncertainty decreased and sheep gained knowledge about the food locations. Our study demonstrates how an arid zone ungulate adjusted its movement and space use behaviour as it gained environmental information about food patch distributions.

Assessing antibody stability in filter paper-preserved blood samples for wildlife disease surveillance in tropical forests - María Fernanda Menajovsky; Gabriela M. Ulloa; Julia E. Fa; Daniel Montes; Stephan Funk; Pedro Mayor (Research in Veterinary Science, 2026)

Probing salty waters: re-assessment of the early stages of calcium carbonate formation in seawater - Anthea I. Arns; David Evans; Ralf Schiebel; Stephan E. Wolf; Anne Jantschke; Maximilian Hansen; Jan Leitner; Hubert Vonhof; Gerald H. Haug (Geochimica et Cosmochimica Acta, 2026)

From simulation to application: enhancing preclinical evaluation of dissolvable microarray patches through PBPK modelling - Maja Railic; Wilhelmus E. A. de Witte; Stephan Schaller; Sarah Toluwanimi Agboola; Ziad Sartawi; Waleed Faisal; Mohamed Elkhashab; Abina Crean; Sonja Vucen (Drug Delivery and Translational Research, 2026)
Dissolvable microarray patches (MAP) represent a promising drug delivery platform; however, the absence of standardised protocols for their preclinical evaluation poses a significant barrier to regulatory approval and clinical translation. Physiologically Based Pharmacokinetic (PBPK) modelling is a powerful tool for predicting drug kinetics following MAP application, addressing key challenges associated with in vitro and in vivo studies such as experimental variability, complex study design, and data extrapolating across different populations. However, adapting PBPK models for dissolvable MAP is inherently complex due to the interplay between microneedle geometry, drug release kinetics, and skin physiology. In this study, an existing dermal PBPK model in MoBi ® was optimised for dissolvable MAP by incorporating microneedle geometry and in vitro release profiles of MAP formulations containing the antihistamines loratadine (LOR) and chlorpheniramine maleate (CPM), as well as the antifungal drug itraconazole (ITZ). Model refinement involved systematically optimising input parameters related to skin thickness and drug-skin diffusion, partitioning and binding, to enhance predictive accuracy. Validation was performed using in vitro permeation testing with porcine skin for CPM and LOR MAP, alongside in vivo preclinical studies in pigs for ITZ MAP. The optimised model demonstrated robust predictive performance across the diverse drug molecules and experimental conditions investigated, highlighting its value as a powerful tool to accelerate preclinical MAP development. Graphical abstract

Enhanced biological desalination by Arthrospira platensis: Role of extracellular polymeric substances in ion adsorption and salt removal - Mostafa E. Elshobary; Roham Sanjari; Sten Littmann; Joachim Henjes; Stephan SW. Ende (Journal of Environmental Management, 2026)

Repairing of in-mold electronics and life cycle assessment - Stephan Harkema; Diana E. Godoi Bizarro; Maarten H. Bakker; Jan P.H. van Delft; Pim R. Ostendorf; Peter A. Rensing; Lia de Simon; A. van Schaik (Resources, Conservation and Recycling, 2026)

Thermal stress has greater impact on the zebrafish skin microbiota than host genotype - Daniel E. Sadler; Phillip C. Watts; Stephan N. van Dijk; Silva Uusi-Heikkilä (Journal of Thermal Biology, 2026)

Fusarium sp. Strain K-23 Alleviates Salt Stress in Arabidopsis thaliana Through its Root Hair Growth-Promoting Effect - Francis C. Onejeme; Adrián González Ortega-Villaizán; Estefanía Rodríguez-Dobreva; Basha Topel Prieto; Manish K. Patel; Selma Guendouzi; Priya Y. N. Reddy; Leonel E. Lopez; José M. Estevez; Karaba N. Nataraja; R. Uma Shaanker; Begoña Benito; et al. (Journal of Plant Growth Regulation, 2025)
Soil salinity is a significant abiotic stress factor that impedes plant growth and crop yield, particularly in arid and semi-arid regions. Recent reports indicate that 8.7% of soils globally and 20–50% of irrigated soils across all continents are affected by salt. This phenomenon jeopardizes the food security of more than 1.5 billion people worldwide. Numerous studies have elucidated the beneficial effects of diverse microbes on plant abiotic stress tolerance. In this study, we report on an observed molecular mechanism involved in the enhanced salt tolerance of Arabidopsis plants co-cultivated with the Fusarium sp. strain K-23. Employing a combination of transcriptomics, phenomics, reverse genetics, and live cell imaging, we elucidated the intricacies of biological processes that influence root growth in the interaction between A. thaliana and the fungus. Moreover, our research corroborated the beneficial effect of the fungus under salt-stress conditions for Arabidopsis and highlighted notable differences compared to previous studies. We utilized an RNA-seq approach to identify biological processes triggered in Arabidopsis roots that interact with K-23, resulting in increased salt tolerance. These experiments necessitated a more comprehensive investigation into the fungal influence on root hair development and elucidated that induced root hair growth was a prerequisite for the enhanced salt stress tolerance conferred by the fungus. Furthermore, we demonstrate that the fungus induces the expression of the NAC transcription factor JUNGBRUNNEN 1 ( JUB1 ). Elevated expression of JUB1 leads to repression of gibberellin biosynthesis, which, in turn, contributes to sustained root hair growth under salt stress conditions, which typically suppresses root hair growth substantially.

Long‐Term Ecological Baselines and Critical Thresholds in Ombrotrophic Peatlands of Europe: Implications for Restoration Strategies - Mateusz Draga; Mariusz Gałka; Klaus‐Holger Knorr; Stephan Glatzel; Bogdan H. Chojnicki; Christian Fritz; Vincent E. J. Jassey; Radosław Juszczak; Hanna Meyer; Bjorn J. M. Robroek; Carrie L. Thomas; Mariusz Lamentowicz (Global Change Biology, 2025)
Maintaining appropriate peatland hydrology, notably through the regulation of the depth to water table (DWT), is crucial for peatland conservation, restoration, and the mitigation of greenhouse gas (GHG) emissions. We assess the long‐term ecological impact of hydrological changes, primarily induced by drainage, in ombrotrophic peatlands across Europe. Our analysis is based on novel palaeoecological data from seven peat cores collected from sites that have experienced varying degrees of anthropogenic disturbance. We reconstructed historical DWT fluctuations using plant macrofossil and testate amoeba analyses at high resolution. By applying Threshold Indicator Taxa Analysis (TITAN) models, we identified species‐specific and community‐level response thresholds to changes in reconstructed water table. This approach revealed two distinct change points: the first, at c . 7 cm DWT, corresponds to hydrological conditions favourable for moisture‐dependent Sphagnum species. The second, at c . 22 cm DWT, is associated with more drought‐adapted plant taxa and signals ecosystem degradation. The interval between these change points represents a transition zone between optimal and suboptimal conditions for peatland functioning. An additional TITAN analysis, designed to identify the timing of major ecological changes, indicates that peatland degradation has intensified over the past two centuries and accelerated in recent decades. Our findings further reveal that plant and testate amoebae communities often remain distinct from those of undisturbed peatlands, even after hydrological restoration. This underscores the importance of preserving sites that still retain near‐natural conditions. Based on our results (and consistent with previous studies) we recommend maintaining the water table close to the surface, i.e., a DWT of approximately 10 cm below the surface as an optimal target for both peatland conservation and restoration. Such conditions not only support ecological integrity but are also associated with reduced GHG emissions and higher peat accumulation rates, reinforcing the role of ombrotrophic peatlands as long‐term carbon sinks.

Inertia-driven flow dynamics across rock fracture intersection: Experimental insights into subsurface reservoir flows - E.A.A.V. Edirisinghe; M.S.A. Perera; D. Elsworth; W. Abu Rowin; Stephan K. Matthai; E. Goudeli (International Journal of Rock Mechanics and Mining Sciences, 2025)

Agroecological practices in United States North Central dairy systems enhance omega-3 and phytonutrient levels in cow's milk - Sree Bhavya Immadi; Muhammad Ahsin; Joseph Vinod Varre; Robert E. Ward; Allen Williams; Stephan Van Vliet (Food Bioscience, 2025)

Identifying and understanding mechanisms in an inhibitory control training in patients with binge-eating-disorder – an exploratory analysis - Sebastian M. Max; Katrin E. Giel; Christian Plewnia; Veronika Lossa; Stephan Zipfel; Kathrin Schag (Appetite, 2025)

Long term assessment of SARS-CoV-2 in wastewater and the transition to evaluate additional viral targets - Ayaaz Amirali; Mark E. Sharkey; Shruti Choudhary; Kristina M. Babler; Cynthia C. Beaver; Pratim Biswas; Kate R. Bowie; Taylor Burke; Benjamin B. Currall; George S. Grills; Hannah G. Healy; Alexander G. Lucaci; et al. (Science of The Total Environment, 2025)

Signatures of Polar Vortex Weakening in the MLTI: A Review - V. L. Harvey; D. Aggarwal; E. Becker; M. Bittner; B. Funke; L. Goncharenko; J. Jia; R. Lieberman; H.-L. Liu; V. Maliniemi; A. Marchaudon; H. Nesse; et al. (Surveys in Geophysics, 2025)
This paper is a collaborative effort that originated at the International Space Science Institute Workshop on “Physical links between Weather and Climate in Space and the Lower Atmosphere” held 22–26 January 2024. Many scientists attended that workshop and contributed their expertise related to polar vortex impacts on upper atmosphere variability. This paper summarizes well-known and newly reported signatures of polar vortex weakening on mesosphere–lower-thermosphere (MLT) temperature, winds, composition, planetary waves, gravity waves, tides, and ionospheric foF2. A variety of observational and modeling results are shown and are consistent with previously published variations in the dynamical and chemical state of the MLT and ionosphere during weak vortex events. We present Superposed Epoch Analysis (SEA) of upper atmosphere diagnostics and phenomena where day 0 is the onset of major SSWs. We also present SEAs where day 0 is the onset of stratopause warmings followed by elevated stratopause events. Our goal in performing two SEAs is to test the sensitivity of 10 hPa versus 1 hPa winds to predict upper atmosphere variability. Results suggest that zonal winds and the semidiurnal migrating solar tide (SW2) in the MLT are more sensitive to zonal wind reversals at 1 hPa rather than 10 hPa. Alternatively, the non-migrating DW2 tide in the equatorial upper mesosphere is best predicted by planetary wave-1 amplitudes in the winter high-latitude upper stratosphere rather than zonal wind reversals. A notable aspect of both SEAs is extremely large event-to-event variability in all diagnostics. Thus, conclusions drawn based on any one event are less robust than those based on many events.

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Synergistic microalgal cocultivation: Boosting flocculation, biomass production, and fatty acids profile of Nannochloropsis oculata and Phaeodactylum tricornutum - Mostafa E. Elshobary; Reham Ebaid; Mohammed Alquraishi; Stephan S.W. Ende (Biomass and Bioenergy, 2025)

Navigating climate change challenges in Sudd wetland fishing communities, South Sudan - John Sebit Benansio; Stephan Michael Funk; John Ladu Lino; Johnson Jiribi Balli; Raphael Filberto Talamuk; John Ohitai Dante; Daniele Dendi; Julia E. Fa; Luca Luiselli (Mitigation and Adaptation Strategies for Global Change, 2025)

Evaluating the performance of multi-omics integration: a thyroid toxicity case study - Sebastian Canzler; Kristin Schubert; Ulrike E. Rolle-Kampczyk; Zhipeng Wang; Stephan Schreiber; Hervé Seitz; Sophie Mockly; Hennicke Kamp; Volker Haake; Maike Huisinga; Martin von Bergen; Roland Buesen; et al. (Archives of Toxicology, 2025)
Multi-omics data integration has been repeatedly discussed as the way forward to more comprehensively cover the molecular responses of cells or organisms to chemical exposure in systems toxicology and regulatory risk assessment. In Canzler et al. (Arch Toxicol 94(2):371–388. https://doi.org/10.1007/s00204-020-02656-y ), we reviewed the state of the art in applying multi-omics approaches in toxicological research and chemical risk assessment. We developed best practices for the experimental design of multi-omics studies, omics data acquisition, and subsequent omics data integration. We found that multi-omics data sets for toxicological research questions were generally rare, with no data sets comprising more than two omics layers adhering to these best practices. Due to these limitations, we could not fully assess the benefits of different data integration approaches or quantitatively evaluate the contribution of various omics layers for toxicological research questions. Here, we report on a multi-omics study on thyroid toxicity that we conducted in compliance with these best practices. We induced direct and indirect thyroid toxicity through Propylthiouracil (PTU) and Phenytoin, respectively, in a 28-day plus 14-day recovery oral rat toxicity study. We collected clinical and histopathological data and six omics layers, including the long and short transcriptome, proteome, phosphoproteome, and metabolome from plasma, thyroid, and liver. We demonstrate that the multi-omics approach is superior to single-omics in detecting responses at the regulatory pathway level. We also show how combining omics data with clinical and histopathological parameters facilitates the interpretation of the data. Furthermore, we illustrate how multi-omics integration can hint at the involvement of non-coding RNAs in post-transcriptional regulation. Also, we show that multi-omics facilitates grouping, and we assess how much information individual and combinations of omics layers contribute to this approach.

Infiltration of secondary treated wastewater into an oxic aquifer: Hydrochemical insights from a large-scale sand tank experiment - Marcel Horovitz; Edinsson Muñoz-Vega; Kay Knöller; Teresa E. Leitão; Christoph Schüth; Stephan Schulz (Water Research, 2024)

Size‐selective harvesting drives genomic shifts in a harvested population - Daniel E. Sadler; Tiina Sävilammi; Stephan N. van Dijk; Phillip C. Watts; Silva Uusi‐Heikkilä (Journal of Fish Biology, 2024)
Overfishing not only drastically reduces the number of fish in an exploited population but is also often selective for body size by removing the largest individuals from a population. Here, we study experimentally the evolutionary effects of size‐selective harvesting using whole‐genome sequencing on a model organism, the zebrafish ( Danio rerio ). We demonstrate genomic shifts in the populations exposed to size‐selective harvesting for five generations and show reduced genetic diversity in all harvested lines, including the control line (non‐size‐selected). We also determine differences in groups of genes related to certain gene ontology annotations between size‐selectively harvested lines, with enrichment in nervous system related genes in the large‐selected lines. Our results illuminate the biological processes underlying fisheries‐induced genetic changes and hence contribute toward the understanding of the changes potentially associated with the vulnerability of an exploited population to future stressors.

Feeling hot is being hot? Comparing the mapping and the surveying paradigm for urban heat vulnerability in Vienna - Sebastian Seebauer; Michael Friesenecker; Thomas Thaler; Antonia E. Schneider; Stephan Schwarzinger (Science of The Total Environment, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Rock glacier distribution across the Himalaya - Stephan Harrison; Darren B. Jones; Adina E. Racoviteanu; Karen Anderson; Sarah Shannon; Richard A. Betts; Ruolin Leng (Global and Planetary Change, 2024)

Description of Asgardarchaeum abyssi gen. nov. spec. nov., a novel species within the class Asgardarchaeia and phylum Asgardarchaeota in accordance with the SeqCode - Daniel Tamarit; Stephan Köstlbacher; Kathryn E. Appler; Kassiani Panagiotou; Valerie De Anda; Christian Rinke; Brett J. Baker; Thijs J.G. Ettema (Systematic and Applied Microbiology, 2024)

Inhibition of pyruvate dehydrogenase accelerates anaerobic glycolysis under postmortem simulating conditions - Mackenzie J. Taylor; Chandler D. Stafford; Jared F. Buhler; David S. Dang; Mohammed A. Alruzzi; Teif A. Najm; Samuel D. Gerrard; Kara J. Thornton; Stephan van Vliet; Samer W. El-Kadi; David E. Gerrard; Sulaiman K. Matarneh (Meat Science, 2024)

Tree demographic strategies largely overlap across succession in Neotropical wet and dry forest communities - Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Dylan Craven; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Bruno Hérault; Catarina C. Jakovac; et al. (Ecology, 2024)
Secondary tropical forests play an increasingly important role in carbon budgets and biodiversity conservation. Understanding successional trajectories is therefore imperative for guiding forest restoration and climate change mitigation efforts. Forest succession is driven by the demographic strategies—combinations of growth, mortality and recruitment rates—of the tree species in the community. However, our understanding of demographic diversity in tropical tree species stems almost exclusively from old‐growth forests. Here, we assembled demographic information from repeated forest inventories along chronosequences in two wet (Costa Rica, Panama) and two dry (Mexico) Neotropical forests to assess whether the ranges of demographic strategies present in a community shift across succession. We calculated demographic rates for >500 tree species while controlling for canopy status to compare demographic diversity (i.e., the ranges of demographic strategies) in early successional (0–30 years), late successional (30–120 years) and old‐growth forests using two‐dimensional hypervolumes of pairs of demographic rates. Ranges of demographic strategies largely overlapped across successional stages, and early successional stages already covered the full spectrum of demographic strategies found in old‐growth forests. An exception was a group of species characterized by exceptionally high mortality rates that was confined to early successional stages in the two wet forests. The range of demographic strategies did not expand with succession. Our results suggest that studies of long‐term forest monitoring plots in old‐growth forests, from which most of our current understanding of demographic strategies of tropical tree species is derived, are surprisingly representative of demographic diversity in general, but do not replace the need for further studies in secondary forests.

Behind the waterfall - Interdisciplinary results from Holley Shelter and their implications for understanding human behavioral patterns at the end of the Middle Stone Age in southern Africa - Gregor D. Bader; Aurore Val; Edwin Gevers; Sara E. Rhodes; Nina Stahl; Stephan Woodborne; Manuel Will (Quaternary Science Reviews, 2024)

Disassembly of in-plastic embedded printed electronics - Stephan Harkema; Peter A. Rensing; Sanne M.D.C. Domensino; Joris M. Vermeijlen; Diana E. Godoi Bizarro; Antoinette van Schaik (Journal of Cleaner Production, 2024)

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

The presence of informed conspecifics improves individual foraging efficiency in naïve sheep - Vartan E. Vartparonian; Stephan T. Leu (Behavioural Processes, 2024)

Climate regulation processes are linked to the functional composition of plant communities in European forests, shrublands, and grasslands - Stephan Kambach; Fabio Attorre; Irena Axmanová; Ariel Bergamini; Idoia Biurrun; Gianmaria Bonari; Maria Laura Carranza; Alessandro Chiarucci; Milan Chytrý; Jürgen Dengler; Emmanuel Garbolino; Valentin Golub; et al. (Global Change Biology, 2024)
Terrestrial ecosystems affect climate by reflecting solar irradiation, evaporative cooling, and carbon sequestration. Yet very little is known about how plant traits affect climate regulation processes (CRPs) in different habitat types. Here, we used linear and random forest models to relate the community‐weighted mean and variance values of 19 plant traits (summarized into eight trait axes) to the climate‐adjusted proportion of reflected solar irradiation, evapotranspiration, and net primary productivity across 36,630 grid cells at the European extent, classified into 10 types of forest, shrubland, and grassland habitats. We found that these trait axes were more tightly linked to log evapotranspiration (with an average of 6.2% explained variation) and the proportion of reflected solar irradiation (6.1%) than to net primary productivity (4.9%). The highest variation in CRPs was explained in forest and temperate shrubland habitats. Yet, the strength and direction of these relationships were strongly habitat‐dependent. We conclude that any spatial upscaling of the effects of plant communities on CRPs must consider the relative contribution of different habitat types.

Heritable differences in abundance of bacterial rhizosphere taxa are correlated with fungal necrotrophic pathogen resistance - Cloe S. Pogoda; Kyle G. Keepers; Stephan Reinert; Zahirul I. Talukder; Brian C. Smart; Ziv Attia; Jason A. Corwin; Kennedy L. Money; Erin C. E. Collier‐zans; William Underwood; Thomas J. Gulya; C. Alisha Quandt; et al. (Molecular Ecology, 2024)
Host–microbe interactions are increasingly recognized as important drivers of organismal health, growth, longevity and community‐scale ecological processes. However, less is known about how genetic variation affects hosts' associated microbiomes and downstream phenotypes. We demonstrate that sunflower ( Helianthus annuus ) harbours substantial, heritable variation in microbial communities under field conditions. We show that microbial communities co‐vary with heritable variation in resistance to root infection caused by the necrotrophic pathogen Sclerotinia sclerotiorum and that plants grown in autoclaved soil showed almost complete elimination of pathogen resistance. Association mapping suggests at least 59 genetic locations with effects on both microbial relative abundance and Sclerotinia resistance. Although the genetic architecture appears quantitative, we have elucidated previously unexplained genetic variation for resistance to this pathogen. We identify new targets for plant breeding and demonstrate the potential for heritable microbial associations to play important roles in defence in natural and human‐altered environments.

Controls on timescales of soil organic carbon persistence across sub‐Saharan Africa - Sophie F. von Fromm; Sebastian Doetterl; Benjamin M. Butler; Ermias Aynekulu; Asmeret Asefaw Berhe; Stephan M. Haefele; Steve P. McGrath; Keith D. Shepherd; Johan Six; Lulseged Tamene; Ebagnerin J. Tondoh; Tor‐Gunnar Vågen; et al. (Global Change Biology, 2024)
Given the importance of soil for the global carbon cycle, it is essential to understand not only how much carbon soil stores but also how long this carbon persists. Previous studies have shown that the amount and age of soil carbon are strongly affected by the interaction of climate, vegetation, and mineralogy. However, these findings are primarily based on studies from temperate regions and from fine‐scale studies, leaving large knowledge gaps for soils from understudied regions such as sub‐Saharan Africa. In addition, there is a lack of data to validate modeled soil C dynamics at broad scales. Here, we present insights into organic carbon cycling, based on a new broad‐scale radiocarbon and mineral dataset for sub‐Saharan Africa. We found that in moderately weathered soils in seasonal climate zones with poorly crystalline and reactive clay minerals, organic carbon persists longer on average (topsoil: 201 ± 130 years; subsoil: 645 ± 385 years) than in highly weathered soils in humid regions (topsoil: 140 ± 46 years; subsoil: 454 ± 247 years) with less reactive minerals. Soils in arid climate zones (topsoil: 396 ± 339 years; subsoil: 963 ± 669 years) store organic carbon for periods more similar to those in seasonal climate zones, likely reflecting climatic constraints on weathering, carbon inputs and microbial decomposition. These insights into the timescales of organic carbon persistence in soils of sub‐Saharan Africa suggest that a process‐oriented grouping of soils based on pedo‐climatic conditions may be useful to improve predictions of soil responses to climate change at broader scales.

Construction of a generalised farm typology to aid selection, targeting and scaling of onfarm research - Kirsty L. Hassall; Frédéric Baudron; Chloe MacLaren; Jill E. Cairns; Thokozile Ndhlela; Steve P. McGrath; Isaiah Nyagumbo; Stephan M. Haefele (Computers and Electronics in Agriculture, 2023)

Monkeypox viral nucleic acids detected using both DNA and RNA extraction workflows - Mark E. Sharkey; Kristina M. Babler; Bhavarth S. Shukla; Samantha M. Abelson; Bader Alsuliman; Ayaaz Amirali; Samuel Comerford; George S. Grills; Naresh Kumar; Jennifer Laine; Jisue Lee; Walter E. Lamar; et al. (Science of The Total Environment, 2023)

OME-Zarr: a cloud-optimized bioimaging file format with international community support - Josh Moore; Daniela Basurto-Lozada; Sébastien Besson; John Bogovic; Jordão Bragantini; Eva M. Brown; Jean-Marie Burel; Xavier Casas Moreno; Gustavo de Medeiros; Erin E. Diel; David Gault; Satrajit S. Ghosh; et al. (Histochemistry and Cell Biology, 2023)
A growing community is constructing a next-generation file format (NGFF) for bioimaging to overcome problems of scalability and heterogeneity. Organized by the Open Microscopy Environment (OME), individuals and institutes across diverse modalities facing these problems have designed a format specification process (OME-NGFF) to address these needs. This paper brings together a wide range of those community members to describe the cloud-optimized format itself—OME-Zarr—along with tools and data resources available today to increase FAIR access and remove barriers in the scientific process. The current momentum offers an opportunity to unify a key component of the bioimaging domain—the file format that underlies so many personal, institutional, and global data management and analysis tasks.

Modulation of resting-state networks following repetitive transcranial alternating current stimulation of the dorsolateral prefrontal cortex - Ahsan Khan; Jochen A. Mosbacher; Stephan E. Vogel; Mira Binder; Michael Wehovz; Arnulf Moshammer; Stefan Halverscheid; Kolja Pustelnik; Michael A. Nitsche; Raymond Kai-Yu Tong; Roland H. Grabner (Brain Structure and Function, 2023)
Transcranial alternating current stimulation (tACS) offers a unique method to temporarily manipulate the activity of the stimulated brain region in a frequency-dependent manner. However, it is not clear if repetitive modulation of ongoing oscillatory activity with tACS over multiple days can induce changes in grey matter resting-state functional connectivity and white matter structural integrity. The current study addresses this question by applying multiple-session theta band stimulation on the left dorsolateral prefrontal cortex (L-DLPFC) during arithmetic training. Fifty healthy participants (25 males and 25 females) were randomly assigned to the experimental and sham groups, half of the participants received individually adjusted theta band tACS, and half received sham stimulation. Resting-state functional magnetic resonance (rs-fMRI) and diffusion-weighted imaging (DWI) data were collected before and after 3 days of tACS-supported procedural learning training. Resting-state network analysis showed a significant increase in connectivity for the frontoparietal network (FPN) with the precuneus cortex. Seed-based analysis with a seed defined at the primary stimulation site showed an increase in connectivity with the precuneus cortex, posterior cingulate cortex (PCC), and lateral occipital cortex. There were no effects on the structural integrity of white matter tracts as measured by fractional anisotropy, and on behavioral measures. In conclusion, the study suggests that multi-session task-associated tACS can produce significant changes in resting-state functional connectivity; however, changes in functional connectivity do not necessarily translate to changes in white matter structure or behavioral performance.

Failure to predict amikacin elimination in critically ill patients with cancer based on the estimated glomerular filtration rate: applying PBPK approach in a therapeutic drug monitoring study - João Paulo Telles; Mariana Suelotto Diegues; Karen Cristina Migotto; Olivia de Souza Borges; Rodrigo Reghini; Brenda Vianna Gavazza; Leonardo Pinto; Pedro Caruso; Ivan Leonardo França e Silva; Stephan Schmidt; Fernanda de Lima Moreira (European Journal of Clinical Pharmacology, 2023)

CME propagation through the heliosphere: Status and future of observations and model development - Manuela Temmer; Camilla Scolini; Ian G. Richardson; Stephan G. Heinemann; Evangelos Paouris; Angelos Vourlidas; Mario M. Bisi; N. Al-Haddad; T. Amerstorfer; L. Barnard; D. Burešová; S.J. Hofmeister; et al. (Advances in Space Research, 2023)

Herbaceous vegetation responses to experimental fire in savannas and forests depend on biome and climate - Zachary J. Gold; Adam F. A. Pellegrini; Tyler K. Refsland; Romina J. Andrioli; Marlin L. Bowles; Dale G. Brockway; Neil Burrows; Augusto C. Franco; Steve W. Hallgren; Sarah E. Hobbie; William A. Hoffmann; Kevin P. Kirkman; et al. (Ecology Letters, 2023)
Fire–vegetation feedbacks potentially maintain global savanna and forest distributions. Accordingly, vegetation in savanna and forest ecosystems should have differential responses to fire, but fire response data for herbaceous vegetation have yet to be synthesized across biomes. Here, we examined herbaceous vegetation responses to experimental fire at 30 sites spanning four continents. Across a variety of metrics, herbaceous vegetation increased in abundance where fire was applied, with larger responses to fire in wetter and in cooler and/or less seasonal systems. Compared to forests, savannas were associated with a 4.8 (±0.4) times larger difference in herbaceous vegetation abundance for burned versus unburned plots. In particular, grass cover decreased with fire exclusion in savannas, largely via decreases in C 4 grass cover, whereas changes in fire frequency had a relatively weak effect on grass cover in forests. These differential responses underscore the importance of fire for maintaining the vegetation structure of savannas and forests.

Diversified innovations in the health sciences: Proposal for a Diversity Minimal Item Set (DiMIS) - Gertraud Stadler; Marie Chesaniuk; Stephanie Haering; Julia Roseman; Vera Maren Straßburger; Schraudner Martina; Ahmad Aisha-Nusrat; Auma Maisha; Banas Kasia; Borde Theda; Buspavanich Pichit; Dewey Marc; et al. (Sustainable Chemistry and Pharmacy, 2023)

Successional shifts in tree demographic strategies in wet and dry Neotropical forests - Nadja Rüger; Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Dylan Craven; Bruno Hérault; et al. (Global Ecology and Biogeography, 2023)
Aim Tropical forest succession and associated changes in community composition are driven by species demographic rates, but how demographic strategies shift during succession remains unclear. Our goal was to identify generalities in demographic trade‐offs and successional shifts in demographic strategies across Neotropical forests that cover a large rainfall gradient and to test whether the current conceptual model of tropical forest succession applies to wet and dry forests. Location Mexico and Central America. Time period 1985–2018. Major taxa studied Trees. Methods We used repeated forest inventory data from two wet and two dry forests to quantify demographic rates of 781 tree species. For each forest, we explored the main demographic trade‐offs and assigned tree species to five demographic groups by performing a weighted principal components analysis to account for differences in sample size. We aggregated the basal area and abundance across demographic groups to identify successional shifts in demographic strategies over the entire successional gradient from very young ( Results Across all forests, we found two demographic trade‐offs, namely the growth–survival trade‐off and the stature–recruitment trade‐off, enabling the data‐driven assignment of species to five demographic strategies. Fast species dominated early in succession and were then replaced by long‐lived pioneers in three forests. Intermediate and slow species increased in basal area over succession in all forests, but, in contrast to the current conceptual model, long‐lived pioneers continued to dominate until the old‐growth stage in all forests. The basal area of short‐lived breeders was low across all successional stages. Main conclusions The current conceptual model of Neotropical forest succession should be revised to incorporate the dominance of long‐lived pioneers in late‐successional and old‐growth forests. Moreover, the definition of consistent demographic strategies that show clear dominance shifts across succession substantially improves the mechanistic understanding and predictability of Neotropical forest succession.

A mid-infrared study of synthetic glass and crystal mixtures analog to the geochemical terranes on mercury - Andreas Morlok; Christian Renggli; Bernard Charlier; Olivier Namur; Stephan Klemme; Maximilian P. Reitze; Iris Weber; Aleksandra N. Stojic; Karin E. Bauch; Harald Hiesinger; Joern Helbert (Icarus, 2023)

The exposed Mule Creek vent deposits record the structure of a volcanic conduit during a hybrid explosive–effusive eruption - Holly E. Unwin; Hugh Tuffen; Fabian B. Wadsworth; Emrys R. Phillips; Mike R. James; Annabelle Foster; Stephan Kolzenburg; Jonathan M. Castro; Lucy A. Porritt (Bulletin of Volcanology, 2023)
Silicic volcanic eruptions commonly begin with the explosive ejection of pyroclastic material, before transitioning to gentler effusion-dominated activity. Well-exposed dissected silicic systems are scarce and poorly studied, hindering the advances in our understanding of the explosive–effusive transition needed to improve interpretations of volcanic unrest and hazard forecasting. The Mule Creek vent (New Mexico, USA) is a dissected silicic conduit that records the processes controlling conduit formation and evolution, and the role tuffisites (fractures filled with variably welded pyroclasts) play in conduit dynamics. Here, we use decimeter-scale photo-mapping of lithostratigraphic units and thin section analysis to differentiate and interpret three dominant emplacement styles during vent evolution. First, there was repeated deposition and erosion of pyroclastic material at the conduit walls, recorded by erosive surfaces in pyroclastic breccia and agglomerates at the conduit margins. Second, sub-vertical domains of dense melt-dominated magma were emplaced and preserved as glass-dominated vitrophyre and brecciated vitrophyre, with the textural hallmarks of assembly from welding of pyroclasts. Finally, the sub-horizontal fracturing of previously deposited lithologies produced laterally cross-cutting tuffisites. The vent deposits track the widening and then narrowing of the conduit through time and reflect progressive insulation and generally higher temperatures towards the conduit center as pyroclasts accumulate. Welding of pyroclastic fill and the formation of dense vitrophyres towards the conduit center lowers deposit porosity and effective wall permeability. This drives localized gas pressure increases and results in gas-driven fracturing, generating tuffisites, which act as transient outgassing pathways. The structure of the Mule Creek vent records an explosive–effusive transition, constraining the processes controlling conduit evolution and aiding our interpretation of volcanic unrest.

Degradation rates influence the ability of composite samples to represent 24-hourly means of SARS-CoV-2 and other microbiological target measures in wastewater - Kristina M. Babler; Mark E. Sharkey; Samantha Abelson; Ayaaz Amirali; Aymara Benitez; Gabriella A. Cosculluela; George S. Grills; Naresh Kumar; Jennifer Laine; Walter Lamar; Erik D. Lamm; Jiangnan Lyu; et al. (Science of The Total Environment, 2023)

Microbial dynamics with CRC progression: a study of the mucosal microbiota at multiple sites in cancers, adenomatous polyps, and healthy controls - Thulasika Senthakumaran; Aina E. F. Moen; Tone M. Tannæs; Alexander Endres; Stephan A. Brackmann; Trine B. Rounge; Vahid Bemanian; Hege S. Tunsjø (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Accumulating evidence has related the gut microbiota to colorectal cancer (CRC). Fusobacterium nucleatum has repeatedly been linked to colorectal tumorigenesis. The aim of this study was to investigate microbial composition in different sampling sites, in order to profile the microbial dynamics with CRC progression. Further, we characterized the tumor-associated F. nucleatum subspecies. Here, we conducted Illumina Miseq next-generation sequencing of the 16S rRNA V4 region in biopsy samples, to investigate microbiota alterations in cancer patients, patients with adenomatous polyp, and healthy controls in Norway. Further, Fusobacterium positive tumor biopsies were subjected to MinION nanopore sequencing of Fusobacterium -specific amplicons to characterize the Fusobacterium species and subspecies. We found enrichment of oral biofilm-associated bacteria, Fusobacterium , Gemella , Parvimonas , Granulicatella , Leptotrichia , Peptostreptococcus , Campylobacter , Selenomonas , Porphyromonas , and Prevotella in cancer patients compared to adenomatous polyp patients and control patients. Higher abundance of amplicon sequence variants (ASVs) classified as Phascolarctobacterium , Bacteroides vulgatus , Bacteroides plebeius , Bacteroides eggerthii , Tyzzerella , Desulfovibrio , Frisingicoccus , Eubacterium coprostanoligenes group, and Lachnospiraceae were identified in cancer and adenomatous polyp patients compared to healthy controls. F. nucleatum ssp. animalis was the dominating subspecies. F. nucleatum ssp. nucleatum , F. nucleatum ssp. vincentii , Fusobacterium pseudoperiodonticum , Fusobacterium necrophorum , and Fusobacterium gonidiaformans were identified in five samples. Several biofilm-associated bacteria were enriched at multiple sites in cancer patients. Another group of bacteria was enriched in both cancer and polyps, suggesting that they may have a role in polyp development and possibly early stages of CRC.

Food-related reward sensitivity across the spectrum of body weight and impulsive eating: Pilot findings from a multi-method approach - Elisabeth J. Leehr; Kathrin Schag; Jule Vogel; Thomas Dresler; Stephan Zipfel; Andreas J. Fallgatter; Martin Hautzinger; Udo Dannlowski; Ann-Christine Ehlis; Katrin E. Giel (Appetite, 2023)

Predicting COVID-19 cases using SARS-CoV-2 RNA in air, surface swab and wastewater samples - Helena M. Solo-Gabriele; Shelja Kumar; Samantha Abelson; Johnathon Penso; Julio Contreras; Kristina M. Babler; Mark E. Sharkey; Alejandro M.A. Mantero; Walter E. Lamar; John J. Tallon; Erin Kobetz; Natasha Schaefer Solle; et al. (Science of The Total Environment, 2023)

Tailored fabrication of quasi-isoporous and double layered α-Fe2O3 thin films and their application in photovoltaic devices - Shanshan Yin; Yuqin Zou; Manuel A. Reus; Xinyu Jiang; Suo Tu; Ting Tian; Ruoxuan Qi; Zhuijun Xu; Suzhe Liang; Yajun Cheng; Julian E. Heger; Matthias Schwartzkopf; et al. (Chemical Engineering Journal, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Perceptions and attitudes towards climate change in fishing communities of the Sudd Wetlands, South Sudan - John Sebit Benansio; Stephan Michael Funk; John Ladu Lino; Johnson Jiribi Balli; John Ohitai Dante; Daniele Dendi; Julia E. Fa; Luca Luiselli (Regional Environmental Change, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Racial and ethnic disparities in diagnostic efficacy of comprehensive genetic testing for sensorineural hearing loss - Michelle M. Florentine; Stephanie L. Rouse; Jihyun Stephans; David Conrad; Josephine Czechowicz; Ian R. Matthews; Anna K. Meyer; Garani S. Nadaraja; Rajan Parikh; Jordan Virbalas; Jacqueline E. Weinstein; Dylan K. Chan (Human Genetics, 2022)
Understanding racial and ethnic disparities in diagnostic rates of genetic testing is critical for health equity. We sought to understand the extent and cause of racial and ethnic disparities in diagnostic efficacy of comprehensive genetic testing (CGT) for sensorineural hearing loss (SNHL). We performed a retrospective cohort study at two tertiary children’s hospitals on a diverse cohort of 240 consecutive pediatric patients (76% publicly insured, 82% non-White) with SNHL of unknown etiology who underwent CGT. Definite and possible genetic diagnoses were assigned for each patient, representing the likelihood of a genetic cause of hearing loss. Associations between diagnostic rates were examined. 3.8 ± 2.1 variants were detected per patient; this frequency did not vary between White/Asian and Hispanic/Black cohorts. Overall, 82% of variants were variants of uncertain significance (VUS). Compared with White and Asian subjects, variants identified among Hispanic and Black children were less likely to be classified as pathogenic/likely pathogenic (15% vs. 24%, p < 0.001), and Hispanic and Black children were less likely to have a definite genetic diagnosis (10% vs. 37%, p < 0.001). The adjusted odds ratio for definite genetic diagnosis in Black and Hispanic children compared with White and Asian children was 0.19. Expanding genetic diagnostic criteria to include predicted deleterious VUSs reduced these disparities between White/Asian and Hispanic/Black children, with comparable molecular diagnostic rates (41% vs. 38%, p = 0.72). However, in silico predictions are insufficiently valid for clinical use. Increased inclusion of underrepresented groups in genetic hearing-loss studies to clinically validate these variants is necessary to reduce racial and ethnic disparities in diagnostic efficacy of comprehensive genetic testing.

An introduction to thermodynamic integration and application to dynamic causal models - Eduardo A. Aponte; Yu Yao; Sudhir Raman; Stefan Frässle; Jakob Heinzle; Will D. Penny; Klaas E. Stephan (Cognitive Neurodynamics, 2022)
In generative modeling of neuroimaging data, such as dynamic causal modeling (DCM), one typically considers several alternative models, either to determine the most plausible explanation for observed data (Bayesian model selection) or to account for model uncertainty (Bayesian model averaging). Both procedures rest on estimates of the model evidence, a principled trade-off between model accuracy and complexity. In the context of DCM, the log evidence is usually approximated using variational Bayes. Although this approach is highly efficient, it makes distributional assumptions and is vulnerable to local extrema. This paper introduces the use of thermodynamic integration (TI) for Bayesian model selection and averaging in the context of DCM. TI is based on Markov chain Monte Carlo sampling which is asymptotically exact but orders of magnitude slower than variational Bayes. In this paper, we explain the theoretical foundations of TI, covering key concepts such as the free energy and its origins in statistical physics. Our aim is to convey an in-depth understanding of the method starting from its historical origin in statistical physics. In addition, we demonstrate the practical application of TI via a series of examples which serve to guide the user in applying this method. Furthermore, these examples demonstrate that, given an efficient implementation and hardware capable of parallel processing, the challenge of high computational demand can be overcome successfully. The TI implementation presented in this paper is freely available as part of the open source software TAPAS.

REPIMPACT - a prospective longitudinal multisite study on the effects of repetitive head impacts in youth soccer - Inga K. Koerte; Roald Bahr; Peter Filipcik; Jolien Gooijers; Alexander Leemans; Alexander P. Lin; Yorghos Tripodis; Martha E. Shenton; Nir Sochen; Stephan P. Swinnen; Ofer Pasternak (Brain Imaging and Behavior, 2022)
Repetitive head impacts (RHI) are common in youth athletes participating in contact sports. RHI differ from concussions; they are considered hits to the head that usually do not result in acute symptoms and are therefore also referred to as “subconcussive” head impacts. RHI occur e.g., when heading the ball or during contact with another player. Evidence suggests that exposure to RHI may have cumulative effects on brain structure and function. However, little is known about brain alterations associated with RHI, or about the risk factors that may lead to clinical or behavioral sequelae. REPIMPACT is a prospective longitudinal study of competitive youth soccer players and non-contact sport controls aged 14 to 16 years. The study aims to characterize consequences of exposure to RHI with regard to behavior (i.e., cognition, and motor function), clinical sequelae (i.e., psychiatric and neurological symptoms), brain structure, function, diffusion and biochemistry, as well as blood- and saliva-derived measures of molecular processes associated with exposure to RHI (e.g., circulating microRNAs, neuroproteins and cytokines). Here we present the structure of the REPIMPACT Consortium which consists of six teams of clinicians and scientists in six countries. We further provide detailed information on the specific aims and the design of the REPIMPACT study. The manuscript also describes the progress made in the study thus far. Finally, we discuss important challenges and approaches taken to overcome these challenges.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Biallelic variants in YRDC cause a developmental disorder with progeroid features - Julia Schmidt; Jonas Goergens; Tatiana Pochechueva; Annika Kotter; Niko Schwenzer; Maren Sitte; Gesa Werner; Janine Altmüller; Holger Thiele; Peter Nürnberg; Jörg Isensee; Yun Li; et al. (Human Genetics, 2021)
The highly conserved YrdC domain-containing protein (YRDC) interacts with the well-described KEOPS complex, regulating specific tRNA modifications to ensure accurate protein synthesis. Previous studies have linked the KEOPS complex to a role in promoting telomere maintenance and controlling genome integrity. Here, we report on a newborn with a severe neonatal progeroid phenotype including generalized loss of subcutaneous fat, microcephaly, growth retardation, wrinkled skin, renal failure, and premature death at the age of 12 days. By trio whole-exome sequencing, we identified a novel homozygous missense mutation, c.662T > C, in YRDC affecting an evolutionary highly conserved amino acid (p.Ile221Thr). Functional characterization of patient-derived dermal fibroblasts revealed that this mutation impairs YRDC function and consequently results in reduced t 6 A modifications of tRNAs. Furthermore, we established and performed a novel and highly sensitive 3-D Q-FISH analysis based on single-telomere detection to investigate the impact of YRDC on telomere maintenance. This analysis revealed significant telomere shortening in YRDC-mutant cells. Moreover, single-cell RNA sequencing analysis of YRDC-mutant fibroblasts revealed significant transcriptome-wide changes in gene expression, specifically enriched for genes associated with processes involved in DNA repair. We next examined the DNA damage response of patient’s dermal fibroblasts and detected an increased susceptibility to genotoxic agents and a global DNA double-strand break repair defect. Thus, our data suggest that YRDC may affect the maintenance of genomic stability. Together, our findings indicate that biallelic variants in YRDC result in a developmental disorder with progeroid features and might be linked to increased genomic instability and telomere shortening.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Systemic mesalazine treatment prevents spontaneous skin fibrosis in PLK2-deficient mice - Manja Newe; Theresa A. Kant; Maximilian Hoffmann; Johanna S. E. Rausch; Luise Winter; Karolina Künzel; Erik Klapproth; Claudia Günther; Stephan R. Künzel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Skin fibrosis is a complex biological remodeling process occurring in disease like systemic sclerosis, morphea, or eosinophilic fasciitis. Since the knowledge about the underlying pathomechanisms is still incomplete, there is currently no therapy, which prevents or reverses skin fibrosis sufficiently. The present study investigates the role of polo-like kinase 2 (PLK2) and the pro-fibrotic cytokine osteopontin (OPN) in the pathogenesis of cutaneous fibrosis and demonstrates the antifibrotic effects of systemic mesalazine treatment in vivo . Isolated primary dermal fibroblasts of PLK2 wild-type (WT) and knockout (KO) mice were characterized in vitro . Skin thickness and histoarchitecture were studied in paraffin-embedded skin sections. The effects of mesalazine treatment were examined in isolated fibroblasts and PLK2 KO mice, which were fed 100 µg/g mesalazine for 6 months via the drinking water. Compared to WT, PLK2 KO fibroblasts displayed higher spontaneous myofibroblast differentiation, reduced proliferation rates, and overexpression of the fibrotic cytokine OPN. In vitro , 72 h of treatment with 10 mmol/L mesalazine induced phenotype conversion in PLK2 KO fibroblasts and attenuated OPN expression by inhibiting ERK1/2. In vivo , dermal myofibroblast differentiation, collagen accumulation, and skin thickening were prevented by mesalazine in PLK2 KO. Plasma creatinine levels indicated good tolerability of systemic long-term mesalazine treatment. The current study reveals a spontaneous fibrotic skin phenotype and ERK1/2-dependent OPN overexpression in PLK2 KO mice. We provide experimental evidence for the antifibrotic effectiveness of systemic mesalazine treatment to prevent fibrosis of the skin, suggesting further investigation in experimental and clinical settings.

The phosphorylated pathway of serine biosynthesis is crucial for indolic glucosinolate biosynthesis and plant growth promotion conferred by the root endophyte Colletotrichum tofieldiae - Sandra E. Zimmermann; Samira Blau; Henning Frerigmann; Stephan Krueger (Plant Molecular Biology, 2021)
Key message Phosphoglycerate Dehydrogenase 1 of the phosphorylated pathway of serine biosynthesis, active in heterotrophic plastids, is required for the synthesis of serine to enable plant growth at high rates of indolic glucosinolate biosynthesis. Abstract Plants have evolved effective strategies to defend against various types of pathogens. The synthesis of a multitude of specialized metabolites represents one effective approach to keep plant attackers in check. The synthesis of those defense compounds is cost intensive and requires extensive interaction with primary metabolism. However, how primary metabolism is adjusted to fulfill the requirements of specialized metabolism is still not completely resolved. Here, we studied the role of the phosphorylated pathway of serine biosynthesis (PPSB) for the synthesis of glucosinolates, the main class of defensive compounds in the model plant Arabidopsis thaliana . We show that major genes of the PPSB are co-expressed with genes required for the synthesis of tryptophan, the unique precursor for the formation of indolic glucosinolates (IG). Transcriptional and metabolic characterization of loss-of-function and dominant mutants of ALTERED TRYPTOPHAN1- like transcription factors revealed demand driven activation of PPSB genes by major regulators of IG biosynthesis. Trans-activation of PPSB promoters by ATR1/MYB34 transcription factor in cultured root cells confirmed this finding. The content of IGs were significantly reduced in plants compromised in the PPSB and these plants showed higher sensitivity against treatment with 5-methyl-tryptophan, a characteristic behavior of mutants impaired in IG biosynthesis. We further found that serine produced by the PPSB is required to enable plant growth under conditions of high demand for IG. In addition, PPSB-deficient plants lack the growth promoting effect resulting from interaction with the beneficial root-colonizing fungus Colletotrichum tofieldiae .

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

Physiological diversity among sympatric, conspecific endosymbionts of coral (Cladocopium C1acro) from the Great Barrier Reef - V. H. Beltrán; E. Puill-Stephan; E. Howells; A. Flores-Moya; M. Doblin; E. Núñez-Lara; V. Escamilla; T. López; M. J. H. van Oppen (Coral Reefs, 2021)

Haploinsufficiency of the HIRA gene located in the 22q11 deletion syndrome region is associated with abnormal neurodevelopment and impaired dendritic outgrowth - Médéric Jeanne; Marie-Laure Vuillaume; Dévina C. Ung; Valerie E. Vancollie; Christel Wagner; Stephan C. Collins; Sandrine Vonwill; Damien Haye; Nora Chelloug; Rolph Pfundt; Joost Kummeling; Marie-Pierre Moizard; et al. (Human Genetics, 2021)

Cross-paradigm connectivity: reliability, stability, and utility - Hengyi Cao; Oliver Y. Chen; Sarah C. McEwen; Jennifer K. Forsyth; Dylan G. Gee; Carrie E. Bearden; Jean Addington; Bradley Goodyear; Kristin S. Cadenhead; Heline Mirzakhanian; Barbara A. Cornblatt; Ricardo E. Carrión; et al. (Brain Imaging and Behavior, 2021)

Repurposing mesalazine against cardiac fibrosis in vitro - Maximilian Hoffmann; Theresa A. Kant; Ramona Emig; Johanna S. E. Rausch; Manja Newe; Mario Schubert; Karolina Künzel; Luise Winter; Erik Klapproth; Rémi Peyronnet; Ursula Ravens; Ali El-Armouche; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Cardiovascular diseases are exacerbated and driven by cardiac fibrosis. TGFβ induces fibroblast activation and differentiation into myofibroblasts that secrete excessive extracellular matrix proteins leading to stiffening of the heart, concomitant cardiac dysfunction, and arrhythmias. However, effective pharmacotherapy for preventing or reversing cardiac fibrosis is presently unavailable. Therefore, drug repurposing could be a cost- and time-saving approach to discover antifibrotic interventions. The aim of this study was to investigate the antifibrotic potential of mesalazine in a cardiac fibroblast stress model. TGFβ was used to induce a profibrotic phenotype in a human cardiac fibroblast cell line. After induction, cells were treated with mesalazine or solvent control. Fibroblast proliferation, key fibrosis protein expression, extracellular collagen deposition, and mechanical properties were subsequently determined. In response to TGFβ treatment, fibroblasts underwent a profound phenoconversion towards myofibroblasts, determined by the expression of fibrillary αSMA. Mesalazine reduced differentiation nearly by half and diminished fibroblast proliferation by a third. Additionally, TGFβ led to increased cell stiffness and adhesion, which were reversed by mesalazine treatment. Collagen 1 expression and deposition—key drivers of fibrosis—were significantly increased upon TGFβ stimulation and reduced to control levels by mesalazine. SMAD2/3 and ERK1/2 phosphorylation, along with reduced nuclear NFκB translocation, were identified as potential modes of action. The current study provides experimental pre-clinical evidence for antifibrotic effects of mesalazine in an in vitro model of cardiac fibrosis. Furthermore, it sheds light on possible mechanisms of action and suggests further investigation in experimental and clinical settings.

Genetic loci underlying quantitative resistance to necrotrophic pathogens Sclerotinia and Diaporthe (Phomopsis), and correlated resistance to both pathogens - Cloe S. Pogoda; Stephan Reinert; Zahirul I. Talukder; Ziv Attia; Erin C. E. Collier-zans; Thomas J. Gulya; Nolan C. Kane; Brent S. Hulke (Theoretical and Applied Genetics, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

“A reference genome assembly and adaptive trait analysis of Castanea mollissima ‘Vanuxem,’ a source of resistance to chestnut blight in restoration breeding” - Margaret Staton; Charles Addo-Quaye; Nathaniel Cannon; Jiali Yu; Tetyana Zhebentyayeva; Matthew Huff; Nurul Islam-Faridi; Shenghua Fan; Laura L. Georgi; C. Dana Nelson; Emily Bellis; Sara Fitzsimmons; et al. (Tree Genetics & Genomes, 2020)

Complete Genome Sequence of Penicillium oxalicum Strain SGAir0226 Isolated from Outdoor Tropical Air in Singapore - Anjali Bansal Gupta; Nicolas E. Gaultier; Ngu War Aung; Rikky W. Purbojati; Elaine L. Oliveira; Anthony Wong; Deepa Panicker; Alexander Putra; Akira Uchida; Daniela I. Drautz-Moses; Stephan C. Schuster (Mycopathologia, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

A Comparison of Evoked and Non-evoked Functional Networks - Jurgen Hebbink; Dorien van Blooijs; Geertjan Huiskamp; Frans S. S. Leijten; Stephan A. van Gils; Hil G. E. Meijer (Brain Topography, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Cholesterol profile in women with premature menopause after risk reducing salpingo-oophorectomy - Natalia Teixeira; Marian J. Mourits; Jan C. Oosterwijk; Ingrid E. Fakkert; Anthony R. Absalom; Stephan J. L. Bakker; Peter van der Meer; Geertruida H. de Bock (Familial Cancer, 2019)

Late Quaternary meltwater pulses and sea level change - Stephan Harrison; David E. Smith; Neil F. Glasser (Journal of Quaternary Science, 2019)
After the Last Glacial Maximum (LGM) global mean sea level (GMSL) rise was characterized by rapid increases over short (decadal to centennial) timescales superimposed on a longer term secular rise and these have been termed meltwater pulses (MWPs). In this paper we review the timing, impact and nature of these and the effects of rapid drainage of large post‐glacial MWPs into the world's oceans. We identify nine MWPs, four of which occurred in three periods of rapid sea level rise (19.5–18.8, 14.8–13.0 and 11.5–11.1 ka BP ). The rest are dated to the period during the Early Holocene sea level rise after 11 ka BP . We show that drainage of the known post‐glacial lakes in total produced less than around 1.2 m of the 125 m of GMSLR since the LGM.

Global guidance on environmental life cycle impact assessment indicators: impacts of climate change, fine particulate matter formation, water consumption and land use - Olivier Jolliet; Assumpció Antón; Anne-Marie Boulay; Francesco Cherubini; Peter Fantke; Annie Levasseur; Thomas E. McKone; Ottar Michelsen; Llorenç Milà i Canals; Masaharu Motoshita; Stephan Pfister; Francesca Verones; et al. (The International Journal of Life Cycle Assessment, 2018)

Emulating mean patterns and variability of temperature across and within scenarios in anthropogenic climate change experiments - Stacey E. Alexeeff; Doug Nychka; Stephan R. Sain; Claudia Tebaldi (Climatic Change, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Patients’ Trust in Physician, Patient Enablement, and Health-Related Quality of Life During Colon Cancer Treatment - Nicole Ernstmann; Markus Wirtz; Anika Nitzsche; Sophie E. Gross; Lena Ansmann; Tristan D. Gloede; Julia Jung; Holger Pfaff; Walter Baumann; Stephan Schmitz; Melanie Neumann (Journal of Cancer Education, 2017)

Meeting the Aichi targets: Pushing for zero extinction conservation - Stephan M. Funk; Dalia Conde; John Lamoreux; Julia E. Fa (Ambio, 2017)
Effective protection of the ~19 000 IUCN-listed threatened species has never been more pressing. Ensuring the survival of the most vulnerable and irreplaceable taxa and places, such as those identified by the Alliance for Zero Extinction (AZE) species and their associated sites (AZEs&s), is an excellent opportunity to achieve the Aichi 2020 Targets T11 (protected areas) and T12 (preventing species extinctions). AZE taxa have small, single-site populations that are especially vulnerable to human-induced extinctions, particularly for the many amphibians. We show that AZEs&s can be protected feasibly and cost-effectively, but action is urgent. We argue that the Alliance, whose initial main aim was to identify AZEs&s, must be followed up by a second-generation initiative that directs and co-ordinates AZE conservation activities on the ground. The prominent role of zoos, conservation NGOs, and governmental institutions provides a combination of all-encompassing knowhow that can, if properly steered, maximize the long-term survival of AZEs&s.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Learning from mistakes in climate research - Rasmus E. Benestad; Dana Nuccitelli; Stephan Lewandowsky; Katharine Hayhoe; Hans Olav Hygen; Rob van Dorland; John Cook (Theoretical and Applied Climatology, 2016)

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Cannabinoid receptor-interacting protein Crip1a modulates CB1 receptor signaling in mouse hippocampus - Stephan Guggenhuber; Alan Alpar; Rongqing Chen; Nina Schmitz; Melanie Wickert; Tobias Mattheus; Anne E. Harasta; Martin Purrio; Nadine Kaiser; Maurice R. Elphick; Krisztina Monory; Werner Kilb; et al. (Brain Structure and Function, 2016)

Temporal dynamics of biotic and abiotic drivers of litter decomposition - Pablo García‐Palacios; E. Ashley Shaw; Diana H. Wall; Stephan Hättenschwiler (Ecology Letters, 2016)
Climate, litter quality and decomposers drive litter decomposition. However, little is known about whether their relative contribution changes at different decomposition stages. To fill this gap, we evaluated the relative importance of leaf litter polyphenols, decomposer communities and soil moisture for litter C and N loss at different stages throughout the decomposition process. Although both microbial and nematode communities regulated litter C and N loss in the early decomposition stages, soil moisture and legacy effects of initial differences in litter quality played a major role in the late stages of the process. Our results provide strong evidence for substantial shifts in how biotic and abiotic factors control litter C and N dynamics during decomposition. Taking into account such temporal dynamics will increase the predictive power of decomposition models that are currently limited by a single‐pool approach applying control variables uniformly to the entire decay process.

Global guidance on environmental life cycle impact assessment indicators: progress and case study - Rolf Frischknecht; Peter Fantke; Laura Tschümperlin; Monia Niero; Assumpció Antón; Jane Bare; Anne-Marie Boulay; Francesco Cherubini; Michael Z. Hauschild; Andrew Henderson; Annie Levasseur; Thomas E. McKone; et al. (The International Journal of Life Cycle Assessment, 2016)

Rare copy number variants and congenital heart defects in the 22q11.2 deletion syndrome - Elisabeth E. Mlynarski; Michael Xie; Deanne Taylor; Molly B. Sheridan; Tingwei Guo; Silvia E. Racedo; Donna M. McDonald-McGinn; Eva W. C. Chow; Jacob Vorstman; Ann Swillen; Koen Devriendt; Jeroen Breckpot; et al. (Human Genetics, 2016)

Computational modeling of Adelta-fiber-mediated nociceptive detection of electrocutaneous stimulation - Huan Yang; Hil G. E. Meijer; Robert J. Doll; Jan R. Buitenweg; Stephan A. van Gils (Biological Cybernetics, 2015)

Selectivity is species-dependent: Characterization of standard agonists and antagonists at human, rat, and mouse adenosine receptors - Mohamad Wessam Alnouri; Stephan Jepards; Alessandro Casari; Anke C. Schiedel; Sonja Hinz; Christa E. Müller (Purinergic Signalling, 2015)

Neuroleptic malignant syndrome and the catatonic dilemma - Stanley N. Caroff; Stephan C. Mann; E. Cabrina Campbell (Psychopharmacology, 2015)

Development of a Cell Permeable Competitive Antagonist of RhoA and CRMP4 binding, TAT-C4RIP, to Promote Neurite Outgrowth - Mohammad R. Khazaei; Samuel Montcalm; Adriana Di Polo; Alyson E. Fournier; Yves Durocher; Stephan Ong Tone (Journal of Molecular Neuroscience, 2015)

Hematological safety of metamizole: retrospective analysis of WHO and Swiss spontaneous safety reports - Lea S. Blaser; Alexandra Tramonti; Pascal Egger; Manuel Haschke; Stephan Krähenbühl; Alexandra E. Rätz Bravo (European Journal of Clinical Pharmacology, 2015)

Unrealistic Optimism, Fatalism, and Risk-Taking in New Zealand Farmers’ Descriptions of Quad-Bike Incidents: A Directed Qualitative Content Analysis - Lynne Clay; E. Jean C. Hay-Smith; Gareth J. Treharne; Stephan Milosavljevic (Journal of Agromedicine, 2015)

Erratum to: Characterization of circulating microparticle-associated CD39 family ecto-nucleotidases in human plasma - Z. Gordon Jiang; Yan Wu; Eva Csizmadia; Linda Feldbrügge; Keiichi Enjyoji; John Tigges; Vasilis Toxavidis; Holger Stephan; Christa E. Müller; C. James McKnight; Alan Moss; Simon C. Robson (Purinergic Signalling, 2014)

Characterization of circulating microparticle-associated CD39 family ecto-nucleotidases in human plasma - Z. Gordon Jiang; Yan Wu; Eva Csizmadia; Linda Feldbrügge; Keiichi Enjyoji; John Tigges; Vasilis Toxavidis; Holger Stephan; Christina E. Müller; C. James McKnight; Alan Moss; Simon C. Robson (Purinergic Signalling, 2014)

First-generation fitness consequences of interpopulational hybridisation in a Great Barrier Reef coral and its implications for assisted migration management - M. J. H. van Oppen; E. Puill-Stephan; P. Lundgren; G. De’ath; L. K. Bay (Coral Reefs, 2014)

Agricultural Quad-bike Incidents: Do Farmworkers Take Risks? - Lynne Clay; E. Jean Hay-Smith; Gareth Treharne; Stephan Milosavljevic (Journal of Agromedicine, 2014)

The global contribution of forage fish to marine fisheries and ecosystems - Ellen K Pikitch; Konstantine J Rountos; Timothy E Essington; Christine Santora; Daniel Pauly; Reg Watson; Ussif R Sumaila; P Dee Boersma; Ian L Boyd; David O Conover; Philippe Cury; Selina S Heppell; et al. (Fish and Fisheries, 2014)
Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published E copath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of forage fish to the catch and value of other commercially targeted predators. Forage fish use and value varied and exhibited patterns across latitudes and ecosystem types. Forage fish supported many kinds of predators, including fish, seabirds, marine mammals and squid. Overall, forage fish contribute a total of about $16.9 billion USD to global fisheries values annually, i.e. 20% of the global ex‐vessel catch values of all marine fisheries combined. While the global catch value of forage fisheries was $5.6 billion, fisheries supported by forage fish were more than twice as valuable ($11.3 billion). These estimates provide important information for evaluating the trade‐offs of various uses of forage fish across ecosystem types, latitudes and globally. We did not estimate a monetary value for supportive contributions of forage fish to recreational fisheries or to uses unrelated to fisheries, and thus the estimates of economic value reported herein understate the global value of forage fishes.

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Impacts of seawater acidification on mantle gene expression patterns of the Baltic Sea blue mussel: implications for shell formation and energy metabolism - Anne K. Hüning; Frank Melzner; Jörn Thomsen; Magdalena A. Gutowska; Lars Krämer; Stephan Frickenhaus; Philip Rosenstiel; Hans-Otto Pörtner; Eva E. R. Philipp; Magnus Lucassen (Marine Biology, 2013)

Dose adjustment in patients with liver cirrhosis: impact on adverse drug reactions and hospitalizations - Carmen C. Franz; Carole Hildbrand; Christa Born; Sabin Egger; Alexandra E. Rätz Bravo; Stephan Krähenbühl (European Journal of Clinical Pharmacology, 2013)

Characteristics of Yersinia enterocolitica biotype 1A strains isolated from patients and asymptomatic carriers - R. Stephan; S. Joutsen; E. Hofer; E. Säde; J. Björkroth; D. Ziegler; M. Fredriksson-Ahomaa (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Species richness declines and biotic homogenisation have slowed down for NW ‐European pollinators and plants - Luísa Gigante Carvalheiro; William E. Kunin; Petr Keil; Jesus Aguirre‐Gutiérrez; Willem Nicolaas Ellis; Richard Fox; Quentin Groom; Stephan Hennekens; Wouter Van Landuyt; Dirk Maes; Frank Van de Meutter; Denis Michez; et al. (Ecology Letters, 2013)
Concern about biodiversity loss has led to increased public investment in conservation. Whereas there is a widespread perception that such initiatives have been unsuccessful, there are few quantitative tests of this perception. Here, we evaluate whether rates of biodiversity change have altered in recent decades in three European countries (Great Britain, Netherlands and Belgium) for plants and flower visiting insects. We compared four 20‐year periods, comparing periods of rapid land‐use intensification and natural habitat loss (1930–1990) with a period of increased conservation investment (post‐1990). We found that extensive species richness loss and biotic homogenisation occurred before 1990, whereas these negative trends became substantially less accentuated during recent decades, being partially reversed for certain taxa (e.g. bees in Great Britain and Netherlands). These results highlight the potential to maintain or even restore current species assemblages (which despite past extinctions are still of great conservation value), at least in regions where large‐scale land‐use intensification and natural habitat loss has ceased.

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

SH3GL2 is frequently deleted in non-small cell lung cancer and downregulates tumor growth by modulating EGFR signaling - Santanu Dasgupta; Jin Sung Jang; Chunbo Shao; Nitai D. Mukhopadhyay; Upneet K. Sokhi; Swadesh K. Das; Mariana Brait; Conover Talbot; Rex C. Yung; Shahnaz Begum; William H. Westra; Mohammad Obaidul Hoque; et al. (Journal of Molecular Medicine, 2013)

Synergistic Bcl-2 inhibition by ABT-737 and cyclosporine A - Pietro E. Cippà; Jivko Kamarashev; Jin Chen; Anna K. Kraus; Stephan Segerer; Laurence Feldmeyer; Thomas Fehr (Apoptosis, 2013)

Recommendation for the discrimination of human-related and natural seismicity - T. Dahm; D. Becker; M. Bischoff; S. Cesca; B. Dost; R. Fritschen; S. Hainzl; C. D. Klose; D. Kühn; S. Lasocki; Th. Meier; M. Ohrnberger; et al. (Journal of Seismology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Allorecognition maturation in the broadcast-spawning coral Acropora millepora - E. Puill-Stephan; B. L. Willis; D. Abrego; J.-B. Raina; M. J. H. van Oppen (Coral Reefs, 2012)

The Garlic and Shallot Core Collection image database of IPK presenting two vegetatively maintained crops in the Federal ex situ genebank for agricultural and horticultural crops at Gatersleben, Germany - Christian Colmsee; E. R. Joachim Keller; Christine Zanke; Angelika Senula; Thomas Funke; Markus Oppermann; Stephan Weise; Uwe Scholz (Genetic Resources and Crop Evolution, 2012)

Here today, not gone tomorrow: long-term effects of corticosterone - Stephan J. Schoech; Michelle A. Rensel; Travis E. Wilcoxen (Journal of Ornithology, 2012)

Sequence variation in the barley genes encoding sucrose synthase I and sucrose phosphate synthase II, and its association with variation in grain traits and malting quality - Inge E. Matthies; Shailendra Sharma; Stephan Weise; Marion S. Röder (Euphytica, 2012)

Potential drug-drug interactions and adverse drug reactions in patients with liver cirrhosis - Carmen C. Franz; Sabin Egger; Christa Born; Alexandra E. Rätz Bravo; Stephan Krähenbühl (European Journal of Clinical Pharmacology, 2012)

Iron oxide mineralogy and stable iron isotope composition in a Gleysol with petrogleyic properties - Tim Mansfeldt; Stephan Schuth; Werner Häusler; Friedrich E. Wagner; Stephan Kaufhold; Mark Overesch (Journal of Soils and Sediments, 2012)

Characteristics of a Shallow River Plume: Observations from the Saco River Coastal Observing System - Charles E. Tilburg; Shaun M. Gill; Stephan I. Zeeman; Amy E. Carlson; Timothy W. Arienti; Jessica A. Eickhorst; Philip O. Yund (Estuaries and Coasts, 2011)

Dau c 1.01 and Dau c 1.02-silenced transgenic carrot plants show reduced allergenicity to patients with carrot allergy - Susanna Peters; Jafargholi Imani; Vera Mahler; Kay Foetisch; Susanne Kaul; Kathrin E. Paulus; Stephan Scheurer; Stefan Vieths; Karl-Heinz Kogel (Transgenic Research, 2011)

Stable isotope analysis of migratory connectivity in a threatened intra-African migrant, the Blue Swallow (Hirundo atrocaerulea) - James Wakelin; Andrew E. McKechnie; Stephan Woodborne (Journal of Ornithology, 2011)

Proposal for a revised taxonomy of the family Filoviridae: classification, names of taxa and viruses, and virus abbreviations - Jens H. Kuhn; Stephan Becker; Hideki Ebihara; Thomas W. Geisbert; Karl M. Johnson; Yoshihiro Kawaoka; W. Ian Lipkin; Ana I. Negredo; Sergey V. Netesov; Stuart T. Nichol; Gustavo Palacios; Clarence J. Peters; et al. (Archives of Virology, 2010)

Effects of Shear Forces and Pressure on Blood Vessel Function and Metabolism in a Perfusion Bioreactor - Markus Hoenicka; Ludwig Wiedemann; Thomas Puehler; Stephan Hirt; Dietrich E. Birnbaum; Christof Schmid (Annals of Biomedical Engineering, 2010)

Older can be better: physiological costs of paternal investment in the Florida scrub-jay - Travis E. Wilcoxen; Raoul K. Boughton; Stephan J. Schoech (Behavioral Ecology and Sociobiology, 2010)

TRPM3 channels provide a regulated influx pathway for zinc in pancreatic beta cells - Thomas F. J. Wagner; Anna Drews; Sabine Loch; Florian Mohr; Stephan E. Philipp; Sachar Lambert; Johannes Oberwinkler (Pflügers Archiv - European Journal of Physiology, 2010)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

The use of aeration as a simple and environmentally sound means to prevent biofouling - Stephan G. Bullard; Sandra E. Shumway; Christopher V. Davis (Biofouling, 2010)

Discrimination and evaluation of lactoferrin and delta-lactoferrin gene expression levels in cancer cells and under inflammatory stimuli using TaqMan real-time PCR - Esthelle Hoedt; Stephan Hardivillé; Christophe Mariller; E. Elass; Jean-Paul Perraudin; Annick Pierce (BioMetals, 2010)

Association mapping and marker development of the candidate genes (1 → 3),(1 → 4)-β-d-Glucan-4-glucanohydrolase and (1 → 4)-β-Xylan-endohydrolase 1 for malting quality in barley - Inge E. Matthies; Stephan Weise; Jutta Förster; Marion S. Röder (Euphytica, 2009)

Evaluation of non-chemical seed treatment methods for the control of Phoma valerianellae on lamb’s lettuce seeds - A. Schmitt; E. Koch; D. Stephan; C. Kromphardt; M. Jahn; H. -J. Krauthausen; G. Forsberg; S. Werner; T. Amein; S. A. I. Wright; F. Tinivella; J. van der Wolf; et al. (Journal of Plant Diseases and Protection, 2009)

Solar UVB and warming affect decomposition and earthworms in a fen ecosystem in Tierra del Fuego, Argentina - JOHANN G. ZALLER; MARTYN M. CALDWELL; STEPHAN D. FLINT; CARLOS L. BALLARÉ; ANA L. SCOPEL; OSVALDO E. SALA (Global Change Biology, 2009)
Combined effects of co‐occurring global climate changes on ecosystem responses are generally poorly understood. Here, we present results from a 2‐year field experiment in a Carex fen ecosystem on the southernmost tip of South America, where we examined the effects of solar ultraviolet B (UVB, 280–315 nm) and warming on above‐ and belowground plant production, C : N ratios, decomposition rates and earthworm population sizes. Solar UVB radiation was manipulated using transparent plastic filter films to create a near‐ambient (90% of ambient UVB) or a reduced solar UVB treatment (15% of ambient UVB). The warming treatment was imposed passively by wrapping the same filter material around the plots resulting in a mean air and soil temperature increase of about 1.2 °C. Aboveground plant production was not affected by warming, and marginally reduced at near‐ambient UVB only in the second season. Aboveground plant biomass also tended to have a lower C : N ratio under near‐ambient UVB and was differently affected at the two temperatures (marginal UVB × temperature interaction). Leaf decomposition of one dominant sedge species ( Carex curta ) tended to be faster at near‐ambient UVB than at reduced UVB. Leaf decomposition of a codominant species ( Carex decidua ) was significantly faster at near‐ambient UVB; root decomposition of this species tended to be lower at increased temperature and interacted with UVB. We found, for the first time in a field experiment that epigeic earthworm density and biomass was 36% decreased by warming but remained unaffected by UVB radiation. Our results show that present‐day solar UVB radiation and modest warming can adversely affect ecosystem functioning and engineers of this fen. However, results on plant biomass production also showed that treatment manipulations of co‐occurring global change factors can be overridden by the local climatic situation in a given study year.

Identification of Sex Pheromone Components of the Hessian Fly, Mayetiola destructor - Martin N. Andersson; Jenny Haftmann; Jeffrey J. Stuart; Sue E. Cambron; Marion O. Harris; Stephen P. Foster; Stephan Franke; Wittko Francke; Ylva Hillbur (Journal of Chemical Ecology, 2009)

Vegetation change during the Mesolithic and Neolithic on the Mizen Peninsula, Co. Cork, south-west Ireland - Timothy M. Mighall; Scott Timpany; Jeffery J. Blackford; Jim B. Innes; Charlotte E. O’Brien; William O’Brien; Stephan Harrison (Vegetation History and Archaeobotany, 2008)

Novel molecular and cellular therapeutic targets in acute lymphoblastic leukemia and lymphoproliferative disease - Valerie I. Brown; Alix E. Seif; Gregor S. D. Reid; David T. Teachey; Stephan A. Grupp (Immunologic Research, 2008)

Targeting endocannabinoid degradation protects against experimental colitis in mice: involvement of CB1 and CB2 receptors - Martin A. Storr; Catherine M. Keenan; Dominik Emmerdinger; Hong Zhang; Birol Yüce; Andrei Sibaev; Federico Massa; Nancy E. Buckley; Beat Lutz; Burkhard Göke; Stephan Brand; Kamala D. Patel; et al. (Journal of Molecular Medicine, 2008)

Differences in saccade-evoked brain activation patterns with eyes open or eyes closed in complete darkness - K. Hüfner; T. Stephan; S. Glasauer; R. Kalla; E. Riedel; A. Deutschländer; T. Dera; M. Wiesmann; M. Strupp; T. Brandt (Experimental Brain Research, 2008)

Eriophyid mite transmission and host range of a Brome streak mosaic virus isolate derived from a full-length cDNA clone - D. Stephan; I. Moeller; A. Skoracka; F. Ehrig; E. Maiss (Archives of Virology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Formation of giant spicules in the deep-sea hexactinellid Monorhaphis chuni (Schulze 1904): electron-microscopic and biochemical studies - Werner E. G. Müller; Carsten Eckert; Klaus Kropf; Xiaohong Wang; Ute Schloßmacher; Christopf Seckert; Stephan E. Wolf; Wolfgang Tremel; Heinz C. Schröder (Cell and Tissue Research, 2007)

Molecular characterization and detection of Vicia cryptic virus in different Vicia faba cultivars - R. Blawid; D. Stephan; E. Maiss (Archives of Virology, 2007)

Validation of a rapid, non-radioactive method to quantify internalisation of G-protein coupled receptors - Maikel Jongsma; Urszula M. Florczyk; Mariëlle C. Hendriks-Balk; Martin C. Michel; Stephan L. M. Peters; Astrid E. Alewijnse (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Role of P2 purinergic receptors in synaptic transmission under normoxic and ischaemic conditions in the CA1 region of rat hippocampal slices - Elisabetta Coppi; Anna Maria Pugliese; Holger Stephan; Christa E. Müller; Felicita Pedata (Purinergic Signalling, 2007)

Chinese mitten crab Eriocheir sinensis in the Baltic Sea—a supply-side invader? - Henn Ojaveer; Stephan Gollasch; Andres Jaanus; Jonne Kotta; Ari O. Laine; Atis Minde; Monika Normant; Vadim E. Panov (Biological Invasions, 2007)

Dynamic causal models of neural system dynamics: current state and future extensions - Klaas E Stephan; Lee M Harrison; Stefan J Kiebel; Olivier David; Will D Penny; Karl J Friston (Journal of Biosciences, 2007)

Upward range extension of Andean anurans and chytridiomycosis to extreme elevations in response to tropical deglaciation - TRACIE A. SEIMON; ANTON SEIMON; PETER DASZAK; STEPHAN R.P. HALLOY; LISA M. SCHLOEGEL; CÉSAR A. AGUILAR; PRESTON SOWELL; ALEX D. HYATT; BRONWEN KONECKY; JOHN E SIMMONS (Global Change Biology, 2007)
High‐alpine life forms and ecosystems exist at the limits of habitable environments, and thus, are especially sensitive to environmental change. Here we report a recent increase in the elevational limit of anurans following glacial retreat in the tropical Peruvian Andes. Three species have colonized ponds in recently deglaciated terrain at new record elevations for amphibians worldwide (5244–5400 m). Two of these species were also found to be infected with Batrachochytrium dendrobatidis ( Bd ), an emerging fungal pathogen causally associated with global amphibian declines, including the disappearance of several Latin American species. The presence of this pathogen was associated with elevated mortality rates of at least one species. These results represent the first evidence of upward expansion of anurans to newly available habitat brought about by recent deglaciation. Furthermore, the large increase in the upper limit of known Bd infections, previously reported as 4112 m in Ecuador, to 5348 m in this study, also expands the spatial domain of potential Bd pathogenicity to encompass virtually all high elevation anuran habitats in the tropical Andes.

Ecological factors influence population genetic structure of European grey wolves - MALGORZATA PILOT; WLODZIMIERZ JEDRZEJEWSKI; WOJCIECH BRANICKI; VADIM E. SIDOROVICH; BOGUMILA JEDRZEJEWSKA; KRYSTYNA STACHURA; STEPHAN M. FUNK (Molecular Ecology, 2006)
Although the mechanisms controlling gene flow among populations are particularly important for evolutionary processes, they are still poorly understood, especially in the case of large carnivoran mammals with extensive continuous distributions. We studied the question of factors affecting population genetic structure in the grey wolf, Canis lupus , one of the most mobile terrestrial carnivores. We analysed variability in mitochondrial DNA and 14 microsatellite loci for a sample of 643 individuals from 59 localities representing most of the continuous wolf range in Eastern Europe. We tested an array of geographical, historical and ecological factors to check whether they may explain genetic differentiation among local wolf populations. We showed that wolf populations in Eastern Europe displayed nonrandom spatial genetic structure in the absence of obvious physical barriers to movement. Neither topographic barriers nor past fragmentation could explain spatial genetic structure. However, we found that the genetic differentiation among local populations was correlated with climate, habitat types, and wolf diet composition. This result shows that ecological processes may strongly influence the amount of gene flow among populations. We suggest natal‐habitat‐biased dispersal as an underlying mechanism linking population ecology with population genetic structure.

Cytotoxic compounds of Physena madagascariensis from the Madagascar rain forest - Shugeng Cao; Andrew Norris; James S. Miller; Fidy Ratovoson; Chris Birkinshaw; Rabodo Andriantsiferana; Vincent E. Rasamison; Stephan Rakotonandrasana; David G. I. Kingston (Natural Product Research, 2006)

Phylogeography of the endemic St. Lucia whiptail lizard Cnemidophorus vanzoi: Conservation genetics at the species boundary - Stephan M. Funk; Julia E. Fa (Conservation Genetics, 2006)

The impact of climate change on lakes in the Netherlands: a review - Wolf M. Mooij; Stephan Hülsmann; Lisette N. De Senerpont Domis; Bart A. Nolet; Paul L. E. Bodelier; Paul C. M. Boers; L. Miguel Dionisio Pires; Herman J. Gons; Bas W. Ibelings; Ruurd Noordhuis; Rob Portielje; Kirsten Wolfstein; et al. (Aquatic Ecology, 2005)

Resistance to apoptosis, increased growth potential, and altered gene expression in cells that survived genotoxic hexavalent chromium [Cr(VI)] exposure - Daryl E. Pritchard; Susan Ceryak; Keri E. Ramsey; Travis J. O'Brien; Linan Ha; Jamie L. Fornsaglio; Dietrich A. Stephan; Steven R. Patierno (Molecular and Cellular Biochemistry, 2005)

A major locus for hereditary prostate cancer in Finland: localization by linkage disequilibrium of a haplotype in the HPCX region - Agnes B. Baffoe-Bonnie; Jeffrey R. Smith; Dietrich A. Stephan; Johanna Schleutker; John D. Carpten; Tommi Kainu; Elizabeth M. Gillanders; Mika Matikainen; Tanya M. Teslovich; Teuvo Tammela; Raman Sood; Andrew M. Balshem; et al. (Human Genetics, 2005)

Specific detection and semi-quantitative analysis of TRPC4 protein expression by antibodies - Veit Flockerzi; Christine Jung; Thomas Aberle; Marcel Meissner; Marc Freichel; Stephan E. Philipp; Wolfgang Nastainczyk; Patrick Maurer; Richard Zimmermann (Pflügers Archiv - European Journal of Physiology, 2005)

Presence of Epstein-Barr virus in esophageal cancer is restricted to tumor infiltrating lymphocytes - Sabine Awerkiew; Axel zur Hausen; Stephan E. Baldus; Arnulf H. Hölscher; Svetlana I. Sidorenko; Sergej I. Kutsev; Herbert J. Pfister (Medical Microbiology and Immunology, 2005)

A major locus for hereditary prostate cancer in Finland: localization by linkage disequilibrium of a haplotype in the HPCX region - Agnes B. Baffoe-Bonnie; Jeffrey R. Smith; Dietrich A. Stephan; Johanna Schleutker; John D. Carpten; Tommi Kainu; Elizabeth M. Gillanders; Mika Matikainen; Tanya M. Teslovich; Teuvo Tammela; Raman Sood; Andrew M. Balshem; et al. (Human Genetics, 2005)

Evaluation of biocontrol preparations and plant extracts for the control of Phytophthora infestans on potato leaves - D. Stephan; A. Schmitt; S. Martins Carvalho; B. Seddon; E. Koch (European Journal of Plant Pathology, 2005)

Transcriptional regulation and processing increase the functional variability of TRPM channels - Annette Lis; Ulrich Wissenbach; Stephan E. Philipp (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Preparation of Microparticles by Micromixers: Characterization of Oil/Water Process and Prediction of Particle Size - Kathrin Schalper; Stephan Harnisch; Rainer H. Mller; Gesine E. Hildebrand (Pharmaceutical Research, 2005)

Key site variables governing the functional characteristics of Dissolved Natural Organic Matter (DNOM) in Nordic forested catchments - Bimal Chatterjee; Egil Gjessing; Jussi V. K. Kukkonen; Hkon E. Larsen; Jrg Luster; Andrea Paul; Stephan Pflugmacher; Mike Starr; Christian E. W. Steinberg; Philippe Schmitt-Kopplin; dm Zsolnay; Rolf D. Vogt; et al. (Aquatic Sciences, 2004)

On the functional significance of the polypeptide PsbY for photosynthetic water oxidation in the cyanobacterium Synechocystis sp. strain PCC 6803 - S. Neufeld; V. Zinchenko; D. P. Stephan; K. P. Bader; E. K. Pistorius (Molecular Genetics and Genomics, 2004)

Behavioural structuring of relatedness in the spotted hyena ( Crocuta crocuta ) suggests direct fitness benefits of clan‐level cooperation - Russell C. Van Horn; Anne L. Engh; Kim T. Scribner; Stephan M. Funk; Kay E. Holekamp (Molecular Ecology, 2004)
Spotted hyenas ( Crocuta crocuta ) are gregarious carnivores that live in multigenerational social groups, called clans, containing one to several matrilines. Members of multiple matrilines within a clan cooperate during dangerous interactions with inter‐ and intraspecific competitors. The evolution of cooperation may be influenced by relatedness between individuals, which in turn is influenced by reproductive skew and mate choice, dispersal and territorial behaviours. Behavioural data exist for spotted hyenas, but corresponding data on patterns of relatedness are unavailable; this lack of data makes it difficult to assess the relative importance of selection pressures favouring cooperative behaviour within and among groups. Therefore we conducted a longitudinal analysis of relatedness within a single large clan of spotted hyenas, as well as a cross‐sectional analysis of relatedness among hyenas from multiple clans. Within a clan, patterns of relatedness reflected known pedigree relationships, and relatedness was higher within than among matrilines, even across generations. Although mean within‐matriline relatedness varied among matrilines, it did not decline with matriline rank. On average, clan members were not related closely, due to high levels of male‐mediated gene flow among clans, and relatedness declined very slightly across clan borders. Low mean relatedness within clans suggests that spotted hyenas cooperate with unrelated clan‐mates against close paternal kin in other clans. Our data also suggest that spotted hyenas must derive large net direct fitness benefits from group living and cooperation.

Gene arrays and temporal patterns of drug response: corticosteroid effects on rat liver - Richard R. Almon; Debra C. DuBois; Keri E. Pearson; Dietrich A Stephan; William J. Jusko (Functional & Integrative Genomics, 2003)

Genetic differentiation of autochthonous populations of Pinus sylvestris (Pinaceae) from the Iberian peninsula - W. Prus-Glowacki; B. R. Stephan; E. Bujas; R. Alia; A. Marciniak (Plant Systematics and Evolution, 2003)

Palatability of marine macro‐holoplankton: Nematocysts, nutritional quality, and chemistry as defenses against consumers - Stephan G. Bullard; Mark E. Hay (Limnology and Oceanography, 2002)
Chemical defenses against consumers have been hypothesized to be common among marine macro‐holoplankton, but few studies have assessed macro‐holoplankton susceptibility to predators or the traits affecting palatability. We used generalist fishes to determine the palatability of fresh tissues, freeze‐dried homogenates, and chemical extracts from 19 species of macro‐holoplankton. Fishes rejected fresh tissues of all the cnidarians, ctenophores, and cyanobacteria we examined but consumed salp and chaetognath tissues. In contrast, fishes consumed homogenates and chemical extracts of all macro‐holoplankton except for the cyanobacterium Trichodesmium sp. We examined nematocysts and low nutritional quality as mechanisms causing rejection of fresh tissues. Once nematocysts were deactivated, fishes consumed cnidarian tentacles, indicating that nematocysts served as defenses. The nutritional quality of macro‐holoplankton varied almost 500‐fold among species and was strongly bimodal, with most macroholoplankton species having ≪0.7 mg soluble protein ml -1 or ≫7 mg ml -1 . In laboratory assays, there was a significant positive relationship between the nutritional quality of artificial foods and their acceptability to fishes. In field assays, reef fishes avoided experimental foods that had a protein content similar to low‐quality macroholoplankton but fed rapidly on higher quality foods. Furthermore, macro‐holoplankton that were high in protein content possessed defensive traits that low‐protein species lacked. Although fresh tissues of most macro‐holoplankton were rejected by generalist fishes, we found evidence of chemical defense only in a cyanobacterium. Thus, chemical defenses were rare among macro‐holoplankton, and rejection for ≫90% of the species we assessed was due to nematocysts or low nutritional quality.

Solar UV‐B radiation affects below‐ground parameters in a fen ecosystem in Tierra del Fuego, Argentina: implications of stratospheric ozone depletion - Johann G. Zaller; Martyn M. Caldwell; Stephan D. Flint; Ana L Scopel; Osvaldo E. Salo; Carlos L. Ballaré (Global Change Biology, 2002)
Stratospheric ozone depletion caused by the release of chlorofluorocarbons is most pronounced at high latitudes, especially in the Southern Hemisphere (including the so‐called ‘ozone hole’). The consequent increase in solar ultraviolet‐B radiation (UV‐B, 280–315 nm) reaching the earth's surface may cause a variety of alterations in terrestrial ecosystems. Most effects might be expected to occur above‐ground since sunlight does not penetrate effectively below‐ground. Here, we demonstrate that solar UV‐B radiation in a fen in Tierra del Fuego (Argentina), where the ozone hole passes overhead several times during the Austral spring, is causing large changes of below‐ground processes of this ecosystem. During the third and fourth year of a manipulative field experiment, we investigated root systems in these plots and found that when the ambient solar UV‐B radiation was substantially reduced, there was a 30% increase in summer root length production and as much as a threefold decrease in already low symbiotic mycorrhizal colonization frequency of the roots compared with plots receiving near‐ambient solar UV‐B. There was also an apparent shift toward older age classes of roots under reduced solar UV‐B. Such large changes in root system behaviour may have decided effects on competition and other ecological interactions in this ecosystem.

Anomalous conditions in the south‐eastern Bering Sea, 1997: nutrients, phytoplankton and zooplankton - Dean A. Stockwell; Terry E. Whitledge; Stephan I. Zeeman; Kenneth O. Coyle; Jeffrey M. Napp; Richard D. Brodeur; Alexei I. Pinchuk; George L. Hunt (Fisheries Oceanography, 2001)
Anomalies in the regional weather over the south‐eastern Bering Sea during spring and summer of 1997 resulted in significant differences in nutrient availability, phytoplankton species composition, and zooplankton abundance over the continental shelf as compared with measurements in the 1980s. Calm winds and the reduction of cloud cover in spring and summer produced a very shallow mixed layer in which nitrate and silicate were depleted after an April diatom bloom. High submarine light levels allowed subsequent phytoplankton growth below the pycnocline and eventual depletion of nitrate from the water column to depths of 70 m or more. Thus, total new production during 1997 may have exceeded that of previous years when nitrate was not depleted below the pycnocline. A bloom of the coccolithophorid, Emiliania huxleyi , was observed in early July in the warm, nutrient‐depleted waters over the middle and inner shelf. Emiliania huxleyi concentrations reached 4.5 × 10 6 cells L –1 by September, and the bloom persisted through the autumn. There was evidence for increased abundance of some species of copepods in 1997 as compared with data from the middle domain in June 1981. The abundance of adult and juvenile euphausiids in 1997 was statistically similar to values measured in 1980 and 1981. However, near‐surface swarms were rarely observed on the inner shelf in August–September 1997. Lack of euphausiid availability in the upper water column may partially explain the August–September mass mortality of planktivorous short‐tailed shearwaters ( Puffinus tenuirostris ) observed on the inner shelf.

Fine mapping of the constitutional translocation t(11;22)(q23;q11) - Isabel Tapia-Páez; Kevin P. O'Brien; Maria Kost-Alimova; Sigrid Sahlén; Darek Kedra; Carl E. G. Bruder; Björn Andersson; Bruce A. Roe; Ping Hu; Stephan Imreh; Elisabeth Blennow; Jan P. Dumanski (Human Genetics, 2000)

Life and Death in the Fast Lane: Demographic Consequences of Road Mortality in the Florida Scrub‐Jay - Ronald L. Mumme; Stephan J. Schoech; Glen E. Woolfenden; John W. Fitzpatrick (Conservation Biology, 2000)
We examined the demographic consequences of road mortality in the cooperatively breeding Florida Scrub‐Jay (Aphelocoma coerulescens ), a threatened species restricted to the oak scrub of peninsular Florida. Between May 1986 and July 1995 we monitored the survival and reproductive success of a color‐banded population of jays along a two‐lane highway at Archbold Biological Station. Annual mortality of breeding adults was 0.38 on road territories, significantly higher than the rate of 0.23 for breeders on nonroad territories. High mortality on road territories appeared to be a direct result of automobile traffic per se and not a consequence of road‐induced changes in habitat characteristics. Mortality was especially high for immigrants without previous experience living along the road: in their first two years as breeders on road territories, naive immigrants experienced annual mortality of 0.50 and 0.45. From year 3 onward, however, annual mortality dropped to 0.29, not significantly different from the rate for birds on nonroad territories. This experience‐dependent decline in road mortality could be caused either by surviving jays learning to avoid automobiles or by selective mortality operating through time (demographic heterogeneity). Proximity to the road had no effect on nesting success beyond its indirect effects on breeder experience and group size. Because the mortality of 30‐ to 90‐day‐old fledglings was significantly higher on road territories than on nonroad territories, however, breeder mortality greatly exceeded production of yearlings on road territories. Roadside territories therefore are sinks that can maintain populations of Florida Scrub‐Jays only via immigration. Because Florida Scrub‐Jays do not avoid roadside habitats and may even be attracted to them, road mortality presents a difficult challenge for the management and conservation of this threatened and declining species.

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Connexin32 gene mutations in X-linked dominant Charcot-Marie-Tooth disease (CMTX1) - E. A. M. Janssen; Stephan Kemp; Gerard W. Hensels; Ongie G. Sie; Christine E. M. de Die-Smulders; Jessica E. Hoogendijk; Marianne de Visser; Pieter A. Bolhuis (Human Genetics, 1997)